Modelo PDCA aplicado a los procesos SGSI del departamento de sistemas del Hospital del IEES de Machala con los estándares ISO/IEC 27001:2007 e 27002:2007 - Armijos Fajardo, Henry Fabián (2010)
The plan-do-check-act is a four-step model for carrying out the change in the policies of information security in the Department of Systems IEES Hospital of Machala.